KNOWING COMPANY SECRETS THROUGH EMPLOYEE POSTS ON SOCIAL MEDIA - Suwinto Johan (Fakultas Hukum, Universitas Diponegoro, 2021)
In today's digital era, many young employees like to upload their activities every day. Uploads in the form of activities, feelings to the outpour of the heart. Company activities include meeting activities, company announcements, to computer screens that display reports that are being made. In addition to company activities, employees also like to upload complaints about work, colleagues, superiors, companies, business partners to customers. There are also employees wearing company uniforms but uploading an activity that does not represent the company but is personal. These posts may leak company secrets or defame the company and coworkers. These posts create legal events. This research uses normative judicial. This study aims to determine whether uploads of company activities or uploads regarding company information can be subject to applicable legal sanctions? This study concludes that uploads that offend personally can be subject to sanctions if any offended party makes a report. Employees upload company secrets, trade secrets, or material company information. Companies can impose sanctions in the form of warning letters to termination of employment. The company's relationship with employees is based on work agreements and company regulations.